2019
DOI: 10.1177/0018726719871995
|View full text |Cite
|
Sign up to set email alerts
|

Emotional expression at work: The effects of strategically expressing anger and positive emotions in the context of ongoing relationships

Abstract: Can anger expressions be functional in the context of ongoing relationships at work – and if so, how and when? Drawing on insights from the dual threshold model and on the emotions-as-social-information theory, we develop and test the theoretical proposition that the strategic expression of both anger and positive emotions in the context of ongoing relationships at work yields benefits for individuals. Across four field studies and using multi-wave and multi-source data, we found that, when paired with the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…Consistent with past work suggesting that "emotion expression patterns can indeed convey important information beyond what is conveyed by the expression of single emotions" (Peralta et al, 2020(Peralta et al, , p. 1494, we reason that upset seekers' positive expressions transmit additional supportrelevant information to providers, beyond that which is transmitted by seekers' negative expressions. As we elaborate in later sections, the special value of positive expressivity within distress-related support-seeking contexts stems from its ability not only to convey additional support-relevant information to providers but also to help providers overcome the specific challenges of listening to expressions of negativity and supporting seekers in distress.…”
Section: Consequences Of Positive Expressivity Within Stress-related supporting
confidence: 89%
“…Consistent with past work suggesting that "emotion expression patterns can indeed convey important information beyond what is conveyed by the expression of single emotions" (Peralta et al, 2020(Peralta et al, , p. 1494, we reason that upset seekers' positive expressions transmit additional supportrelevant information to providers, beyond that which is transmitted by seekers' negative expressions. As we elaborate in later sections, the special value of positive expressivity within distress-related support-seeking contexts stems from its ability not only to convey additional support-relevant information to providers but also to help providers overcome the specific challenges of listening to expressions of negativity and supporting seekers in distress.…”
Section: Consequences Of Positive Expressivity Within Stress-related supporting
confidence: 89%
“…They found that political group leaders' expressions of anger, contempt, and disgust in combination produced followers' violence against other groups. Although not specific to leadership, Peralta et al (2019) through three survey studies found that strategically expressing anger, when paired with the strategic expression of positive emotions, enhanced both peer-and self-perceptions of cooperation, which further contributed to work effectiveness. Future research could also experimentally manipulate the combinations of leader anger and other emotional expressions to test how leader anger expression interacts with other emotional expressions to produce unique leadership outcomes.…”
Section: From Facial Expression Alone To a Broader Scope And Holistic Investigationmentioning
confidence: 97%
“…The parameters in the two algorithms were identical, and the results of the traditional algorithm experiment and the improved algorithm experiment were compared when the agent located the target in the maze [ 23 ]. The average reward received by the emotional agent after locating the target using the conventional algorithm and the improved policy algorithm is compared in Figures 8 and 9 , along with the number of trials required to locate the target successfully [ 24 ].…”
Section: Experimental Deconstruction Of Emotional Cognitionmentioning
confidence: 99%